2006
DOI: 10.1111/j.1745-7270.2006.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Salicylic Acid-responsive <italic>Cis</italic>-acting Elements and W-boxes in Salicylic Acid Induction of <italic>VCH3</italic> Promoter in Transgenic Tobaccos

Abstract: A salicylic acid (SA)-inducible VCH3 promoter was recently identified from grapevine (Vitis amurensis) that contains two inverse SA-responsive cis-acting elements and four W-boxes. To further demonstrate the roles of these elements, four fragments with lengths from -1187, -892, -589, -276 to +7 bp were fused with the b-glucuronidase (GUS) reporter gene and transferred to Nicotiana tobacum, together with another four VCH3 promoter fragments with mutation in the two inverse SA-responsive elements. The functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The inverse salicylic acid (SA)-responsive elements (GCAGT, inverse to as-1 element) and the W-box in the Vitis amurensis VCH3 promoter were found to be involved in SA induction (Li et al 2006). Interestingly, the comparative sequence analysis of the enhancer region of the DaMVSgt4 promoter with other Caulimovirus promoters revealed that DaMVSgt4 promoter contains three as-1 elements, which makes this promoter unique compared with other caulimovirus promoters (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The inverse salicylic acid (SA)-responsive elements (GCAGT, inverse to as-1 element) and the W-box in the Vitis amurensis VCH3 promoter were found to be involved in SA induction (Li et al 2006). Interestingly, the comparative sequence analysis of the enhancer region of the DaMVSgt4 promoter with other Caulimovirus promoters revealed that DaMVSgt4 promoter contains three as-1 elements, which makes this promoter unique compared with other caulimovirus promoters (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple CAREs present in the promoter sequences of CsTPS2 , CsTPS9 and CsTPS19 were identified as possibly involved in JA, SA or ABA responsiveness. For example, G‐boxes (CACGTG), required for JA‐mediated expression regulation (Kim et al ., 1992 ; Endt et al ., 2007 ), W‐boxes (TTGACC) associated with responsiveness to SA (Li et al ., 2006 ) and ABRE motifs, related to ABA responsiveness (Lenka et al ., 2009 ), were present in all three promoters. The wound‐responsive WUN motif was found in p CsTPS9 and p CsTPS19 but not in p CsTPS2 , and this might play an as‐yet‐unknown role in the different responses to the mechanical damage inflicted by herbivores from different feeding guilds.…”
Section: Discussionmentioning
confidence: 99%
“…It's possible that, in addition to auxin transport impairments, the lazy1 branch angle phenotype is connected to reduced cell elongation in abaxial branch tissues as a result of high SA concentrations. The Arabidopsis LAZY1 promoter region also has several SA responsive W-Box and WLE1 elements -(T)TGAC(C/T) and TGACA respectively -suggesting SA may have a direct role in regulating LAZY1 expression 43,44 . However, our RNAseq data uncovered DEGs more tangentially, rather than directly, related to SA biosynthesis and signaling.…”
Section: Discussionmentioning
confidence: 99%